Thyroid FNA performed by cytopathologists accompanied by radiologists guiding the ultrasound provide high-level quality results: A retrospective observational study - Borges, Felipe Abrantkoski; Camilo-Júnior, Deolino João; Yamamoto, Fábio Massahito [UNESP]; Xavier-Júnior, José Cândido C. [UNESP] (Elsevier, 2022)
Background: On thyroid cytology, false negative and false positive rates are considered parameters for quality control. Nevertheless, there are few studies about medical professional involved in this procedure. We conducted a 4-year cytohistological correlation of thyroid specimens in a single institution. To describe cytological and histological correlation where radiologists guide the ultrasound (US) and cytopathologists perform the thyroid fine needle aspiration (FNA). Methods: Retrospective observational study of thyroid specimens in a Brazilian countryside setting. The ultrasound was performed by radiologists, and the FNA was performed by pathologists. All cases were reviewed by two pathologists following the Bethesda Reporting System for Reporting Thyroid Cytopathology and the World Health Organization's Classification of Tumours of Endocrine Organs. Clinical information, such as sex, age, location, and ultrasound data, was collected from our reports. Results: From a total of 3265 patients, 3703 nodules (391 patients showed more than one nodule) were submitted to FNA. For correlation, there were 168 surgical thyroidectomy specimens. The risk of malignancy for the Bethesda system categories were: nondiagnostic/unsatisfactory = 0/4 (0%); benign = 1/38 (2.6%); atypia of undetermined significance or follicular lesion of undetermined significance = 2/20 (10.0%); follicular neoplasm or suspicious for follicular neoplasm = 3/16 (18.7%); suspicious for malignancy = 63/67 (94.0%); and malignant = 22/23 (95.6%). Conclusion: High-level quality results can be accomplished with cooperation between cytopathologists performing thyroid FNA accompanied by radiologists guiding the ultrasound.
Keywords: Biopsy; Cytology; Fine-needle; Pathology; Quality control; Thyroid neoplasms